Characterization and Yield Testing of Two Prospective Varieties and Three Comparative Varieties of Kyuri Cucumber (Cucumis sartivus L.) in the Highlands - Putra, Muhammad Rizki Ana; Zainudin, Agus; Septia, Erfan Dani; Astutik, Anik Widya (Universitas Muhammadiyah Malang, 2023)
Cucumber (Cucumis sativus L.) is one type of vegetable from the cucurbitaceae family that has been grown by farmers in Indonesia. The research was conducted for 4 months from September 23 to December 13, 2022 in one of the experimental fields owned by PT Aditya Sentana Agro. The purpose of this study was to determine whether the 2 candidate varieties CI-88 and CI-87 of kyuri cucumber tested would show significant differences in characters from 3 comparison varieties F1 MK 01, F1 MK 02, F1 MK 03 and to determine whether the results obtained from the 2 candidate varieties CI-88 and CI-87 of kyuri cucumber to be used as varieties and produced. This study consisted of 2 genotypes of hybrid variety candidates CI-88 and CI-87 and 3 comparison varieties namely F1 MK 01, F1 MK 02 and F1 MK 03 which were used as treatments. The three comparison varieties were used because they were in high demand in the market so that they had a high selling value and had a good response from farmers. Qualitative characteristics observed were stem shape, leaf shape, flower color, fruit shape, fruit skin color, fruit flesh color, and fruit taste test. The results of observations of qualitative character traits are presented in the form of tables and picture documentation. The results of quantitative characterization observations include stem diameter, fruit weight per plant, fruit weight per fruit, fruit diameter, fruit length, number of fruits per plant, leaf width, leaf length, age from flowering and age from harvest. The results of the two candidate varieties tested have the opportunity to be developed and registered as new varieties because the results obtained are comparable to the comparator varieties already on the market..